PENGARUH PENDIDIKAN KESEHATAN TENTANG PIJAT BAYI TERHADAP PERILAKU IBU DALAM MEMIJATKAN BAYI SECARA MANDIRI DI DESA ARGOSARI KECAMATAN SENDURO - Lisa Cristian Dewi Natalia; Muthmainah Zakiyyah; Nova Hikmawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Baby massage is a traditional art that combines nurturing touches on babies carried out by parents, caregivers, or therapists through movements and massage techniques. In its development, baby massage has been associated with touch between parents and children, because it can create affection between parents and babies, reduce anxiety levels, and increase physical abilities and self-confidence. This study aims to determine the effect of health education about infant massage on the behavior of mothers in massaging babies independently in Argosari Village, Senduro. This research was a quantitative study with a pre-experimental research design. The research sample consisted of 24 infant mothers using a purposive sampling approach. The research was carried out by conducting a pretest, then the respondents were given health education, then an observation (posttest) was carried out using an observation sheet. Data analysis was carried out using the Wilcoxon test because the data distribution was not normal. The results of this study are that there is a significant influence between health education about baby massage on the mother's behavior in massaging the baby independently. The health center needs to include material about infant massage in health promotion which is carried out regularly in the village to increase public knowledge about infant massage.